Intercropping of medicinal and aromatic plants in coconut gardens - Basavaraju, T.B.; Nanjappa, H.V.; Umesha, K.; Vasundhara, M.; Arulraj, S. (Journal of Plantation Crops, 2011)
A field study was conducted at Horticulture Research Station, Arsikere, Karnataka during 2006-07 to 2008-09 to identify suitable medicinal and aromatic plants for intercropping in coconut gardens of maidan tract of Karnataka. The experiment consisted of 14 medicinal and aromatic crops viz., Kalmegh (Andrographis paniculata), Makoi (Solanum nigrum), Coleus (Coleus forskohlii), Garden rue (Ruta graveolens), Lepidium (Lepidium sativum), Tulsi (Ocimum sanctum), Arrow root (Maranta arundinaceae), Kacholam (Kaemferia galanga), Cowhage (Mucuna pruriens), Roselle (Hibiscus sabdariffa), Ambrette (Abelmoschus moschatus), Citronella (Cymbopogon winteranus), Lemon grass (Cymbopogon flexuosus) and Vetiver grass (Vetiveria zizanoides). The yield of all the medicinal and aromatic crops grown as intercrop in coconut garden were reduced compared to their sole crop yields. The reduction in yield was less in lemon grass (6.4 %), tulsi (23.5 %), arrow root (23.9 %), vetiver grass (25.1 %), kalmegh (25.7 %), makoi (29.1 %), citronella (30.2 %) and garden rue (30.5 %). The nut yield of coconut was improved with intercropping of medicinal and aromatic crops. The andrographolide content in kalmegh (4.40 to 3.20 %), rutin alkaloids in garden rue (1.68 to 1.40 %) and oil content in lepidium (19.60 to 17.23 %) were significantly reduced when grown as intercrops in coconut garden as compared to sole crop. However, the forskohlin content in coleus (0.43 to 0.61 %) and essential oil content in ambrette (0.24 to 0.29 %) were significantly increased by intercropping. In other medicinal and aromatic crops, the quality parameters were not significantly influenced by intercropping. The intercropping system of growing lemon grass under coconut recorded the highest net income (Rs. 91,561/ha) and B:C ratio (2.89) followed by garden rue (Rs. 81,865/ha and 2.79), tulsi (Rs. 77,472/ha and 2.71), kalmegh (Rs. 75,163/ha and 2.56), arrow root (Rs. 72,211/ha and 2.28) and makoi (Rs. 67,058/ha and 2.68). Hence, intercropping of lemon grass, garden rue, tulsi, kalmegh, arrow root and makoi with coconut can be recommended for maidan tract of Karnataka.